Lung abscess or empyema? Taking a closer look - Hassan, M; Asciak, R; Rizk, R; Shaarawy, H; Gleeson, F; Rahman, N (BMJ Publishing Group, 2018)
I would like to present three cases of patients who presented with symptoms of lower respiratory tract infection, fever and cough productive of small amount of sputum. The three patients had complained of symptoms for at least 2 weeks before presentation. The chest X-rays showed large encysted collections (figure 1A) which required chest CT to delineate the source of the abnormality. The CT studies (case 1: figure 1B, C; case 2: figure 2A and case 3: figure 2C) caused prolonged discussion between the treating clinicians with opinions divided on the nature of the lesion in each case being either an encysted empyema or a large peripheral lung abscess. Clinically, the differentiation between empyema and lung abscess was important because empyema is treated with tube drainage which is only resorted to in limited situations in lung abscess with the attendant risk of creating a bronchopleural fistula or extending the infection to the pleura.